Bapakism in Jokowi’s pandemic handling : the cultural dimension - Muhamad Arif (2020)
The Jokowi administration has been widely criticised for its handling of the COVID-19 pandemic, given its slow response, as well as inconsistent and unclear policies. Is there a cultural explanation for the president’s less than satisfactory posture during this pandemic period?